Pemanfaatan Google Data Studio dalam Visualisasi Biografi Periwayat Hadis - Qaem Aulassyahied; Asep Rahmat Fauzi; Yaumil Falihah (Masyarakat Berdaya dan Inovasi, 2022)
Among the challenges in the development of hadith scholarship is the lack of use of technology to display scientific information related to hadith and its surroundings. For example, data regarding the biographies of hadith narrators is still in the form of classical descriptions contained in traditional books. In fact, looking at the technology that has developed to this day, these historical data can be better visualized so that they are easy to access, understand and measure. The purpose of this paper is to utilize digital technology -in this case Google data studio- to visualize historical information on hadith narrators or better known as Tārīkh ar-Ruwwāh science. The use of Google Data Studio was taught to students of Darussalam Notoprajan Islamic Boarding School, Yogyakarta in the following stages: First, conducting an assessment to determine the participants' level of understanding of the science of Tarikh ar-Ruwwah and Google Data Studio. Second, based on the first data, a workshop will be held. The first material covers understanding related to the science of the Ar-Ruwwat Date. The second material is an introduction to Google Data Studio and its functions and advantages. Third, Conduct practical guidance on using Google Data Studio to visualize historical information on hadith narrators contained in classical books. Visualization of historical data of hadith narrators with Google Data Studio makes it easier for students to see the hadith transmission journey that occurs for each narrator because the visualization of the location between one narrator and another narrator is clearly illustrated by the visualization of the location. Apart from that, Google Data Studio also increases respect and appreciation for the efforts of hadith narrators in compiling hadiths in books, because the students can also estimate how far the locations traveled by these narrators